Nanoemulsion delivery systems: impact of emulsifier type on curcumins bioaccessibility during in vitro digestion - Gonçalves, Raquel Filipa Silva (2019)
This study was supported by the Portuguese Foundation for Science and Technology (FCT) under the scope of the Project PTDC/AGR-TEC/5215/2014, the strategic funding of UID/BIO/04469/2019 unit and BioTecNorte operation (NORTE-01-0145-FEDER-000004) funded by the European Regional Development Fund under the scope of Norte2020 - Programa Operacional Regional do Norte.